The Relationship Between Maternal Knowledge Parenting Patterns and Exclusive Breastfeeding with The Incidence of Stunting in Toddlers in The Work Area of The Urban Health Center Tanjung Priok North Jakarta. - Owan Ratna Permaha; Diah Argarini; Rizki Hidayat (Jurnal Kesehatan dr. Soebandi, 2023)
Stunting is a condition in which babies are shorter than their peers, With a prevalence of 36.4%, Indonesia ranks third among Southeast Asian nations. The aim is to determine the relationship between the level of mother's knowledge, exclusive breastfeeding and parenting style with the incidence of stunting in toddlers . This study used a descriptive analytic method with a cross-sectional approach, a sample of 81 toddlers stunted and non-stunted toddlers. The sample technique uses a purposive sampling technique. The instrument used is scale likert questionnaire. The results of the study showed that there was a relationship between the mother's knowledge level pvalue = 0.000, exclusive breastfeeding pvalue = 0.003 and parenting style pvalue = 0.000 to the incidence of stunting in toddlers. There is a significant relationship between the level of mother's knowledge, exclusive breastfeeding and parenting style with the incidence of stunting. Monitoring and assessing program implementation is necessary, as is periodically treating nutrition cases. Outreach initiatives and support for moms of young children are also important ways to raise awareness of the value of exclusive breastfeeding. Keyword: Maternal Knowledge Level, Exclusive Breastfeeding, Parenting, Incidence of Stunting